How and Why Affective and Reactive Virtual Agents Will Bring New Insights on Social Cognitive Disorders in Schizophrenia? An Illustration with a Virtual Card Game Paradigm - Oker, Ali; Prigent, Elise; Courgeon, Matthieu; Eyharabide, Victoria; Urbach, Mathieu; Bazin, Nadine; Amorim, Michel-Ange; Passerieux, Christine; Martin, Jean-Claude; Brunet-Gouet, Eric (Frontiers in Human Neuroscience, 2015)
In recent decades, many studies have shown that schizophrenia is associated with severe social cognitive impairments affecting key components, such as the recognition of emotions, theory of mind, attributional style and metacognition. Most studies investigated each construct separately, precluding analysis of the interactive and immersive nature of real-life situation. Specialized batteries of tests are under investigation to assess social cognition which is thought now as a link between neurocognitive disorders and impaired functioning. However, this link accounts for a limited part of the variance of real life functioning. To fill this gap, advances in virtual reality and affective computing have made it possible to carry out experimental investigations of naturalistic social cognition, in controlled conditions, with good reproducibility. This approach is illustrated with the description of a new paradigm based on an original virtual card game in which subjects interpret emotional displays from a female virtual agent, and decipher her helping intentions. Independent variables concerning emotional expression in terms of valence and intensity were manipulated. We show how several useful dependant variables, ranging from classic experimental psychology data to metacognition or subjective experiences records, may be extracted from a single experiment. Methodological issues about the immersion into a simulated intersubjective situation are considered. The example of this new flexible experimental setting with regards to the many constructs recognized in social neurosciences, constitutes a rationale for focusing on this potential intermediate link between standardized tests and real life functioning, and also for using it as an innovative media for cognitive remediation.